Telaah Nilai Kemanusiaan Perspektif Ilmu Hadis - Muhammad Yusuf; Damanhuri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This research discusses human values ​​in the Prophet's hadith in terms of the quality of the hadith in the history, sanad, and matan and the content of the hadith. This research aims to find the results of partial analysis and simultaneous analysis of the Prophet's hadith regarding husbands' good deeds toward their wives and other people. The partial analysis in the research aims to determine the quality of the hadith sanad and matan. After partial analysis, the quality of hadith in sanad and matan found the sanad authentic and the matn hadith too authentic. Simultaneous analysis was conducted to determine whether the hadith also existed in other histories with different historical paths. The results simultaneously hadiths in the research only came from one friend, namely Aisyah R.A. and the hadith in the research is included in the ahad ghorib hadith category. The content of the hadith can be known through discussion hadith jurisprudence so that it can reveal the true message the Prophet conveys. The hadith in the research means that a husband must do good to his wife and others